CO2 capture on aminosilane functionalized alumina-extracted residue of catalytic gasification coal ash. (15th April 2021) - Li, Xiangyu; Wang, Zhiqing; Feng, Ru; Huang, Jiejie; Fang, Yitian
Abstract: The technology of alumina-extraction from coal ash provides an effective way for re-utilization of coal based solid waste as resource. However, one of the most serious challenges that this technology face is the harmless treatment of alumina-extracted residue (AR). Considering the structure and properties of AR, a scheme was proposed to make the AR as a potential sorbent for CO2, and in order to achieve enhanced CO2 adsorption performance, the AR was functionalized with (3-aminopropyl) triethoxysilane (APTES). Moreover, the effects of amine grafting amount and temperature on CO2 adsorption capacity of sorbents were investigated. The results show that at 25 °C and 100% CO2, the sample obtained by adding 12 mmol of APTES presented the maximum CO2 adsorption capacity of 1.23 mmol/g. The sorbent can be regenerated successfully at 110 °C and maintain a stable uptake in 5 repeated adsorption–desorption cycles. These results suggested that APTES functionalized alumina-extracted residue is a potential excellent sorbent for CO2 absorption. Highlights: Alumina-extracted residue of coal ash (AR) was directly used to prepare CO2 sorbents for the first time. Low-cost solid waste sorbents with excellent sorption performance were prepared by chemical grafting. A good cycle stability and the highest CO2 sorption capacity were obtained by AR-12APS. The CO2 sorption mechanism of AR sorbents grafting with amine was discussed.